Assessment of an empirical bob-skeleton steering model - Sawade, C.; Turnock, S.; Forrester, A.; Toward, M. (Procedia Engineering, 2014)
The sport of Skeleton involves the headfirst decent on a Bobsleigh ice track, whereby an athlete lies face forward on a sled with two runners. The athlete steers by applying reactive control movements with his or her shoulders and knees. There is a limited understanding of how these control movements effect the sled direction (yaw), which currently restricts advances in sled design. These limitations exist due to a lack of understanding at the ice-runner interaction contact point. Without knowing exactly how the runners create friction and why, runner design and athlete control is misunderstood. This paper discusses the measurement and analysis of on-track recorded data of various sled motion, forces and steering input parameters. These parameters have been used to develop an empirical `steering` model, with the integration of athlete steering forces to determine sled reaction and response from steering input. Validation of the model shows a good relationship between real and approximated sled yaw throughout the descent. Such a model gives an insight into which forces are the primary cause of sled direction change and therefore how best to manipulate and change such forces to maximise control for the athlete. Future work includes validation of various runner friction coefficients so that control of different runners can be explored.